Agricultura familiar e supermercados: a experiência de valorização dos alimentos de origem familiar no estado da Bahia - Morais, João Rafael Gomes de (2025)
The aim of this article is to analyze the institutional changes that took place in the state of Bahia between 2011 and 2021, based on the experience of Coopercuc’s products entering the supermarket market. The collection and analysis of qualitative data included bibliographic research on the interactions between retail and family farmers, documentary research on Bahia's public policies, and nine semi-structured interviews with Coopercuc leaders, focusing on the impact of these changes. The case of Bahia demonstrates that in institutional environments favorable to family farming, commercial relationships with medium and small-scale retailers, as exemplified by Coopercuc’s experience, can be more advantageous than those established with large retail chains. In these interactions, in addition to the price and quality of food products, the reputation and prestige of suppliers are key factors, as they contribute to reducing the risks and uncertainties associated with such partnerships.